The influences of skin visco‐elasticity, hydration level and aging on the formation of wrinkles: a comprehensive and objective approach. Issue 1 (4th June 2012) - Choi, Jae Woo; Kwon, Soon Hyo; Huh, Chang Hun; Park, Kyoung Chan; Youn, Sang Woong
Abstract : Background: Various skin parameters including skin visco‐elasticity and hydration level affect the formation of wrinkles. Objective: The aim of this study was to investigate the comprehensive and objective relationship between age, skin visco‐elasticity, hydration level, and the occurrence of wrinkles using bioengineering equipments for the first time. Methods: A total number of 97 healthy women were included in this study. Age, Fitzpatrick skin type, skin mechanical parameters obtained with Cutometer ® (R0 R9), hydration level measured with Corneometer ®, as well as wrinkle parameters (SEsm, SEr, SEsc, and SEw) assessed with Visioscan ®, were analyzed with the Pearson's correlation test. Results: The skin fluidity (R6) increased while the elastic recovery ratio (R7) decreased with the age. The wrinkle parameter (SEw) also increased with the age. The higher skin hysteresis values (R4 and R9) coincided with the higher SEw values. Skin hydration significantly lowered the hysteresis (R9), the wrinkles (SEw), and the depth of wrinkle furrows (R3mr). Conclusion: The elderly have less elastic skin and more wrinkles. Skin hysteresis most closely related with the degree of wrinkles. Drier skin showed more wrinkles and deeper furrows, with wider intervals. On the basis of these objective findings, we propose several skin parameters associated with wrinkles, and hypothesize the mechanism of wrinkle generation.